PERSEPSI KONSUMEN TERHADAP KUALITAS PELAYANAN PADA RESTORAN CEPAT SAJI McDonald’s DI JAKARTA - Nurul Giswi Karomah; Susi Oktafiani; Siti Nur Rohmah (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2022)
This study aims to provide the descriptive, depiction systematic view, factual and the accurate descriptions of the facts, characteristics and relationships between phenomena regarding to consumer perception and service quality at McDonald’s fast food in Jakarta. The type of the research used in this study is exploration descriptive qualitative research. The sampling technique used is Accidental Sampling, with the number of samples in this study as many as 80 person of McDonald’s customers. The data from this study were sourced from questionnaires distributed in the form of google form. The questionnaires was made based on to reliability and validity test. Data analysis technique used in this study are Data Collection, Data Reduction and Data Display. The results of the research showed the respondent’s responses to Consumer Perception at McDonald’s Jakarta fast food restaurants were Good, seen from the average total score of 334 which was included in the range of 275-339 with the assessment criteria Good. Meanwhile, respondent’s responses to Service Quality at McDonald’s Jakarta fast food restaurants were Excellent, seen from the average total score of 340,2 which included in the range of 340-400 with the assessment criteria Excellent. Suggestions can be given in this study are McDonald’s Jakarta fast food restaurants are expected to hold training or do the guidance to their employees so that the have better skills and management so that the consumers will be trust, comfortable and assured of the service quality of McDonald’s Jakarta fast food restaurants so that they can maintain consumers perception about service quality.